2021
DOI: 10.3390/rs13081545
|View full text |Cite
|
Sign up to set email alerts
|

Extended Pseudo Invariant Calibration Site-Based Trend-to-Trend Cross-Calibration of Optical Satellite Sensors

Abstract: Satellite sensors have been extremely useful and are in massive demand in the understanding of the Earth’s surface and monitoring of changes. For quantitative analysis and acquiring consistent measurements, absolute radiometric calibration is necessary. The most common vicarious approach of radiometric calibration is cross-calibration, which helps to tie all the sensors to a common radiometric scale for consistent measurement. One of the traditional methods of cross-calibration is performed using temporally an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Recent research has confirmed that the twenty high-reflectance desert sites are still relevant targets for on-orbit calibration, nearly 30 years later [28]. Out of the original twenty PICS in the Sahara Desert and the Arabian Peninsula, six have been endorsed by the Committee on Earth Observation Satellites (CEOS) as the highest-quality standard reference sites for post-launch vicarious calibration [29].…”
Section: Pseudoinvariant Calibration Sites (Pics)mentioning
confidence: 99%
“…Recent research has confirmed that the twenty high-reflectance desert sites are still relevant targets for on-orbit calibration, nearly 30 years later [28]. Out of the original twenty PICS in the Sahara Desert and the Arabian Peninsula, six have been endorsed by the Committee on Earth Observation Satellites (CEOS) as the highest-quality standard reference sites for post-launch vicarious calibration [29].…”
Section: Pseudoinvariant Calibration Sites (Pics)mentioning
confidence: 99%
“…The CEOS WGCV has agreed upon and endorsed a set of six such desert PICS for long-term satellite monitoring and reference purposes, and more information can be found at https://calvalportal.ceos.org/pics_sites and within the PICS reports published therein. New PIC usage methodologies and techniques in evaluation stages include extended PICS (EPICS) and super or cluster PICS with the goal of increasing PIC scene analysis data (e.g., Vuppula, 2017;Khakurel et al, 2021).…”
Section: Radiometric Calibration Targetsmentioning
confidence: 99%
“…The application of the absolute surface reflectance model of Algodones Dunes and the Salton Sea to other satellites, Spectral Band Adjustment Factor (SBAF), was implemented. SBAF is a compensating factor for matching the spectral response of two sensors [39] described in this section. Even when the satellite sensors used for the validation look at the same target through similar spectral regions, they respond differently in terms of spectral response.…”
Section: Estimation Of Spectral Band Adjustment Factormentioning
confidence: 99%